Perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) based composites organic battery - Dere, A. (Elsevier, 2018)
A new organic battery was fabricated using perylene-3,4,9,10-tetracarboxylic dianhydride organic semiconductor and copper chloride electrolyte. The perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) organic semiconductor based composites were synthesized for various contents of black carbon (BC). The structural properties of the PTCDA:BC composites were confirmed by XRD, FTIR, EDX and SEM analyses. The dielectric constants and alternating electrical conductivity (AC) of the composites were increased using BC dopant. The electrical properties of prepared batteries were by current-voltage characteristics. The open circuit voltage, V-oc of the battery is increased from 0.17 V to 0.45 V, while the short circuit current, I-sc is changed from 12 mA to 25 mA. The battery having PTCDA: BC (80.20) ratio exhibited a highest maximum power, P-max of 3.08 mW. The obtained results indicate that PTCDA:BC composites based batteries can be used in micropower energy applications.
Keywords: Organic semiconductor; Battery